Panicle inclination influences pollination stability of rice (Oryza sativa L.). (2nd January 2020) - Win, Aung; Tanaka, Takashi S. T.; Matsui, Tsutomu
ABSTRACT: Rice pollination occurs when pollen grains fall by gravity from the anther onto the stigma and has been thought to be assured under suitable conditions. However, the position of the stigma relative to the anther pores may affect pollination. The inclination of panicle, that is quite usual in agricultural scene, may change the relative position of anther and stigma. We investigated the effect of panicle inclination on pollination stability. Pots of rice at flowering stage were tilted at one of the four inclinations (0° = control, 15°, 30°, and 45°). We assessed pollination (numbers of total and germinated pollen grains on the stigma) and morphology of dehisced anthers. Inclination significantly affected the number of total and germinated pollen grains on the stigma: as it increased from 0° to 45°, the percentage of florets with <20 total pollen grains on the stigma (TP20) increased from 36.6% to 59.9%, and that of florets with <10 germinated pollen grains on the stigma (GP10) increased from 26.6% to 58.9%. Both an increase in TP20 and a decrease in the rate of pollen germination were major causes of the increase in GP10. Inclination did not affect anther morphology. A panicle inclination of ≥30°could greatly reduce rice production because rice fertilization requires >10 germinated pollen grains on the stigma. Uprightness of the panicle at flowering should be an important objective in rice breeding and production. Abbreviations: TP20: percentage of florets with <20 total pollen grains on the stigma; GP10: percentage of florets with <10 germinated pollen grains on the stigma Graphical abstract: